Atmospheric aerosol analysis at the PIXE–RBS beamline in the University of Jordan Van de Graaff accelerator (JUVAC). (31st January 2019) - Sa'adeh, Hanan; Chiari, Massimo
Abstract : The University of Jordan Van de Graaff accelerator (JUVAC) was devoted many years ago to promote scientific research through the installation of several beamlines based on nuclear techniques. It constitutes the first and unique, till now, ion beam analysis facility in Jordan. Among these techniques, the JUVAC has recently installed, with the financial and technical aid of the International Atomic Energy Agency, a combination of particle‐induced X‐ray emission (PIXE) and Rutherford backscattering spectrometry (RBS). A new X‐ray detector has been installed, and the system has been tested for aerosol analysis using a set of thin MicroMatter standards. This manuscript includes a brief description of the combined PIXE–RBS beamline with some results, particularly those obtained by PIXE. The low‐energy proton beam adds a technical limitation to attain optimum analytical performance. However, a simulation of the RBS spectrum of protons on aerosol filter indicates that the RBS measurement for some elements (e.g., Pb) can replace the PIXE one.